2022
DOI: 10.3390/ijerph192417019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air Pollution Control Auditing on Reducing Carbon Emissions: Evidence from China

Abstract: Analyzing the carbon-emission-reduction mechanism from the perspective of air pollution control auditing is of great practical significance for China to implement the dual-carbon strategy. Based on the panel data of 30 Chinese provinces from 2004 to 2018, we examine whether and how the auditing of air pollution control has an impact on carbon emission reduction by using multiple regression method and the mediating analysis. Our analyses show that air pollution control auditing can significantly restrain carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…These instruments have undergone continuous refinement and optimization, as elucidated by Ref. [ 29 ]. According to the People's Bank of China, the quantum of green loans in China soared to an impressive RMB 22.03 trillion by the close of 2022, underscoring the significant role played by green credit within the broader green finance framework.…”
Section: Resultsmentioning
confidence: 99%
“…These instruments have undergone continuous refinement and optimization, as elucidated by Ref. [ 29 ]. According to the People's Bank of China, the quantum of green loans in China soared to an impressive RMB 22.03 trillion by the close of 2022, underscoring the significant role played by green credit within the broader green finance framework.…”
Section: Resultsmentioning
confidence: 99%
“…Auditing affects the environment [9][10][11]. Most studies discuss the role of environmental auditing in terms of its strict enforcement and monitoring role [12].…”
Section: Introductionmentioning
confidence: 99%
“…It also promotes agricultural technological progress to reduce agricultural carbon emission intensity (Liu et al, 2023). Zhao et al (2022), on the other hand, found that air pollution audits curb carbon emissions but have no effect on carbon emission intensity. In summary, these scholars explore special audits' impacts on carbon emissions.…”
Section: Introductionmentioning
confidence: 99%